2014
DOI: 10.1093/jrr/rru077
|View full text |Cite
|
Sign up to set email alerts
|

Combination of macrophage inflammatory protein 1 alpha with existing therapies to enhance the antitumor effects on murine hepatoma

Abstract: Existing therapies such as irradiation or sorafenib have limited success in the treatment of hepatocellular carcinoma (HCC) due to tumor recurrence and metastasis. Therefore, combination with other therapeutics is often considered. Macrophage inflammatory protein-1 alpha (MIP-1α) is a member of a family of chemoattractant cytokines that can induce the migration of monocytes, which in turn can play a role in fighting tumors. This study investigated whether intravenous injection of MIP-1α in conjunction with irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…44 While there is literature suggesting MIP-1α may also play a role in tumor cell migration, its proimmune effects may be dominant in the context of IL-12 administration. In support of this idea, Jeong et al 45 found that combining i.v. MIP-1α therapy with preestablished methods of treatment for hepatocellular carcinoma, such as irradiation or sorafenib, significantly enhanced antitumor immunity dependent on increased CD8 + , CD107A + , and CD11C + cells.…”
Section: Discussionmentioning
confidence: 92%
“…44 While there is literature suggesting MIP-1α may also play a role in tumor cell migration, its proimmune effects may be dominant in the context of IL-12 administration. In support of this idea, Jeong et al 45 found that combining i.v. MIP-1α therapy with preestablished methods of treatment for hepatocellular carcinoma, such as irradiation or sorafenib, significantly enhanced antitumor immunity dependent on increased CD8 + , CD107A + , and CD11C + cells.…”
Section: Discussionmentioning
confidence: 92%
“…They are located on human chromosome 17 and encode the macrophage inflammatory proteins-1α (MIP-1α) and human CC ligand 3-like protein 1 (CCL3L1), respectively, which belong to the family of chemotactic cytokines known as chemokines. MIP-1α is produced by macrophages and has the ability to induce the migration of monocytes, which then differentiate into dendritic cells (DCs) to recognize an antigen and activate tumor-specific T-cell responses via their potent antigen-presenting capacity to efficiently recognize and kill stem-like cancer cells [ 21 26 ]. When the level of MIP-1α decreases, the antitumor activity will be weakened resulting in promoting tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…CCL3 encoded the macrophage inflammatory proteins-1α (MIP-1α), which was produced by macrophages and had the ability to induce the migration of monocytes. Then the monocytes differentiated into dendritic cells (DCs) to recognize an antigen and activate tumor-specific T-cell responses via their potent antigen-presenting capacity to efficiently recognize and kill stem-like cancer cells [ 21 26 ]. The second one could promote tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…This stimulates TNF-α and IL-6 production and an inflammatory response [ 125 ]. In murine models, lung metastasis was reportedly prevented and survival improved when irradiation was delivered with intravenously administered recombinant macrophage inflammatory protein-1 alpha (MIP-1α) [ 126 ]. Further research is required to determine the effect of RT on TAMs in the TME.…”
Section: Modulation Of the Tam Population By Current Hcc Therapiesmentioning
confidence: 99%